Investigation of carbon dioxide capture with aqueous piperazine on a post combustion pilot plant–Part I: Energetic review of the process. (August 2015) - Rabensteiner, Markus; Kinger, Gerald; Koller, Martin; Gronald, Günter; Hochenauer, Christoph
Highlights: The pilot plant allows a practical operation. Operation with real flue gases of the gas- and coal-fired power plant. Absorber and desorber have nearly industrial heights. Advantages of piperazine over monoethanolamine can be identified. Low solvent flow rates and energy demands are possible. Abstract: 37.6 wt% piperazine (7 molal) was investigated in a PCC-test facility on the power plant in Dürnrohr, Austria. Through the use of real power plant flue gas and the well-conceived dimensions of the test facility, industry-related conditions for full scale applications can be provided. Deviations from measurement results, generated on other test facilities in which piperazine was tested, are discussed scientifically. The specific energy consumption for solvent regeneration can be reduced to 3.17 GJ/tCO2 (without absorber intercooler and multi-stage flash), resulting in an energy saving of 14% in comparison to 30 wt% MEA. The low CO2 absorption heat of piperazine and the low sensible heat are crucial for the low energy consumption. The optimal solvent flow rate is 20% lower in comparison to that of 30 wt% MEA, resulting in less pumping and cooling demand. Especially for the regenerated solvent there is a risk of solidification. Even a small temperature reduction of the regenerated solvent in operation can lead to failure. A sudden system failure leads to a rapid solidification. Endangered areas have to be trace heated. A detailed parameter study and an emission measurement on the pilot plant will be presented in Part II of this paper.